Sales Forecasting of the Local Cultural Product Tanjak Melayu in Rokan Hulu Using the Trend Moment Method to Support Sustainable UMKM Marketing Strategies (Program Studi Pendidikan Teknologi Infromasi UMK, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in strengthening Indonesia’s regional economy and preserving cultural identity through creative industries. One of the prominent local cultural products is Tanjak Melayu, a traditional Malay headpiece produced in Rokan Hulu Regency, Riau. However, inconsistent market demand often leads to production inefficiencies and unstable marketing performance. This study aims to forecast the sales of Tanjak Melayu using the Trend Moment method integrated with seasonal adjustment analysis to support sustainable MSME marketing strategies. The dataset used consists of monthly sales records from January 2023 to December 2024, analyzed using quantitative forecasting techniques. The resulting trend equation, Y = 145.55 + 1.4087X, indicates an average monthly increase of 1.4 units in sales volume. Model validation produced a MAPE value of 3.78%—categorized as excellent accuracy—and an RMSE value of 9.08, reflecting a low prediction error compared to actual sales. The findings demonstrate that the Trend Moment method effectively captures both the upward sales trend and seasonal fluctuations, with demand peaks occurring in November and December. This research provides practical insights for MSME actors in optimizing production planning and marketing schedules, and theoretical contributions by highlighting the applicability of simple statistical forecasting for culture-based small enterprises toward sustainable economic development.